2017
DOI: 10.1007/s12250-017-3984-9
|View full text |Cite
|
Sign up to set email alerts
|

Human leukemia antigen-A*0201-restricted epitopes of human endogenous retrovirus W family envelope (HERV-W env) induce strong cytotoxic T lymphocyte responses

Abstract: Human endogenous retrovirus W family (HERV-W) envelope (env) has been reported to be related to several human diseases, including autoimmune disorders, and it could activate innate immunity. However, there are no reports investigating whether human leukemia antigen (HLA)-A*0201 restriction is involved in the immune response caused by HERV-W env in neuropsychiatric diseases. In the present study, HERV-W env-derived epitopes presented by HLA-A*0201 are described with the potential for use in adoptive immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…A more thorough evaluation for CfERV peptides in the future seems warranted. In humans, CTL have been demonstrated against ERV-derived peptides, supporting their presentation by HLA class I molecules (Mullins and Linnebacher, 2012; Schiavetti et al, 2002; Tu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A more thorough evaluation for CfERV peptides in the future seems warranted. In humans, CTL have been demonstrated against ERV-derived peptides, supporting their presentation by HLA class I molecules (Mullins and Linnebacher, 2012; Schiavetti et al, 2002; Tu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although peptides were used in many recent studies with concentrations ranging from 10–100 μg/ml, such as 20 μg/ml ( 51 ), 25 μg/ml ( 28 ), and 50 μg/ml ( 52 ), it is not always the case that the higher peptide concentration incubated DCs induced the higher activity of T cells. As early as 1964, Mitchison’s immunological study found that high immune doses often failed to induce ideal immune protection effect, which was called “high zone tolerance” ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abundant interferon-γ-secreting T cells were also detected after stimulation of these peptides for several weeks. These data demonstrate that Syncytin-1 peptides (such as W, Q, and T peptides) can induce HLA-A2.1-restricted CD8 + CTL and could be a potential target for astrocytoma immunotherapy ( 98 ). On the other hand, the cytotoxic T lymphocytes induced by Syncytin-1 could be a potential mechanism for inflammatory abnormalities in the CNS.…”
Section: Syncytin-1 Could Cause Inflammatory Abnormalities In Neuropsmentioning
confidence: 81%